2010
DOI: 10.1364/oe.18.020673
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow-repetition-rate, high-energy, polarization-maintaining, Er-doped, ultrashort-pulse fiber laser using single-wall-carbon-nanotube saturable absorber

Abstract: An ultralow-repetition-rate, all-polarization-maintaining (PM), Er-doped, ultrashort-pulse fiber laser was demonstrated using a single-wall-carbon-nanotube polyimide film. Using a ring cavity configuration, output pulses with pulse energy of 0.7-2.6 nJ were obtained at an ultralow repetition rate of 943-154 kHz for a fiber length of 0.1-1.3 km. A novel θ (theta) cavity configuration was proposed, which enabled us to reduce the required fiber length by half. A repetition rate of 132 kHz was achieved using this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 19 publications
0
27
1
Order By: Relevance
“…They demonstrated the possibility of passive mode locking in long cavities due to saturable absorbers, such as single-wall carbon nanotubes [25,40,41], semiconductor saturable absorber mirrors [42][43][44], and non-linear optical loop mirrors [45]. It was experimentally and theoretically confirmed that passively mode-locked fiber master oscillators give rise to a broad variety of generation regimes in different cavity configurations [46][47][48][49][50][51][52][53], including generation of single and multiple pulses over a cavity round-trip, pulses with various duration, envelope shape, and spectrum width.…”
Section: Ultra-long Mode-locked Fiber Lasers: Discussionmentioning
confidence: 99%
“…They demonstrated the possibility of passive mode locking in long cavities due to saturable absorbers, such as single-wall carbon nanotubes [25,40,41], semiconductor saturable absorber mirrors [42][43][44], and non-linear optical loop mirrors [45]. It was experimentally and theoretically confirmed that passively mode-locked fiber master oscillators give rise to a broad variety of generation regimes in different cavity configurations [46][47][48][49][50][51][52][53], including generation of single and multiple pulses over a cavity round-trip, pulses with various duration, envelope shape, and spectrum width.…”
Section: Ultra-long Mode-locked Fiber Lasers: Discussionmentioning
confidence: 99%
“…Schematic of extra-long mode-locked fibre laser: F2 -All-wave fibre, length of 2,6 km. New results obtained in the experiments (Kobtsev et al, 2008c) with relatively high energy of pulses directly in a passively mode-locked laser stimulated further investigations in this area Zhang et al, 2009;Lin et al, 2011;Song et al, 2011;Ai et al, 2011;Kobtsev et al, 2009;Senoo et al, 2010;Kelleher et al, 2009;L. Chen et al, 2009;Nyushkov et al, 2010;Kobtsev et al, 2010a;Ivanenko et al, 2010).…”
Section: Review Of Recent Progress In Mode-locked Fibre Lasers With Hmentioning
confidence: 99%
“…The time-bandwidth product was about 236, which was ~750 times the transform limit, assuming a sech 2 profile. In (Senoo et al, 2010), passive mode-lock regime was also used in a full-PM fibre cavity of novel -configuration with the use of saturable absorber (single-wall carbon nanotubes). Generation in an ultra-long cavity with anomalous dispersion was reported in (Li et al 2010).…”
Section: Review Of Recent Progress In Mode-locked Fibre Lasers With Hmentioning
confidence: 99%
“…Using the polyimide film dispersed with SWNTs, we demonstrated an ultralow-repetition rate, high-energy, all-polarization maintaining, ultrashort pulse Er-doped fiber laser. 17) A novel theta cavity configuration was proposed and a repetition rate as low as 132 kHz was demonstrated.…”
Section: Progress Of Ultrashort Pulse Fiber Lasermentioning
confidence: 99%